Psychometric Analysis of a Brief measure of Emotional Intelligence (EQ-i-M20) in Teenagers from Lima - Navarro-Loli, Jhonatan S. (2023)
The research aimed to assess if the EQ-i-M20 presents evidence of validity regarding its internal structure, measurement invariance between men and women, and acceptable reliability. The sample consisted of 788 adolescents between 11 and 18 years old from an educational institution in Lima (Peru). The internal structure was evaluated by the Exploratory Structural Equation Modeling (ESEM), both the oblique model and the bifactor, the invariance of measurement with a multiple ESEM group, and its reliability using the α and ω. The results indicate that in men and women. the original factor structure of five oblique factors is replicated, that it has an acceptable degree of measurement invariance, and the reliability values are satisfactory. In conclusion, the EQ-i-M20 is an instrument with adequate psychometric properties.